Assessing of physiological arousal and cognitive anxiety toward academic performance: The application of catastrophe model - Vitasari, Prima; Muhammad Nubli, Abdul Wahab; Herawan, Tutut; Suriya Kumar, Sinnadurai; Ahmad, Othman; Muhamad Ghani, Awang (Elsevier Ltd., 2011)
The Catastrophe model in which the theory attempts to explain the interaction of physiological arousal cognitive anxiety affect on sport's performance. The model is important to understand the influence of anxiety upon performance. This research proposes a model to understand the effect of anxiety upon academic performance. The research consists with finding on the Catastrophe model of anxiety upon sport's performance. A total 135 students were participated in this study conducted during 2nd semester. The physiological arousal was measured using heart rate sensor and respiration sensor. Meanwhile, cognitive anxiety was measure using State Trait Anxiety Inventory (STAI) and Study Anxiety Scale (SAS). Furthermore, Grade Point Average (GPA) is employed to predict students’ academic performance. For assessment, the Pearson correlation was used to assess the physiological arousal and cognitive anxiety toward academic performance. The finding shows that high level of physiological arousal and cognitive anxiety is a significant factor that creates low academic performance. Based on the finding, it is concluded that the model can be use to comprehend of relationship between anxiety toward academic performance.